Supporting School Readiness Naturally: Exploring Executive Function Growth in Nature Preschools - Zamzow, Jenna; Ernst, Julie (International Journal of Early Childhood Environmental Education, 2020)
This study utilized the Minnesota Executive Function Scale to quantitatively explore the influence of nature preschools on executive function skills, which are a critical component of school readiness. Executive function skills are malleable skills that allow goal setting and follow through, skills that determine success in school and beyond. Four nature and two non-nature preschools participated in the study. These six preschools shared a child-centered, play-based approach toward supporting holistic development across the domains. The primary difference between the nature and non-nature preschools was in the proportion of the day spent outdoors and the location of the outdoor play time (in nature v. in maintained outdoor settings). Results suggest significant executive function skill growth among the nature preschool participants; this growth was similar to that observed in the non-nature preschool participants. Additionally, children across the nature and non-nature preschools had growth in executive function skills that exceeded what would be expected in typically developing children. Implications for further research are discussed.
Keywords: Child Development; Educational Environment; Executive Function; Natural Resources; Outdoor Education; Preschool Children; Preschool Education; School Readiness